Pengaruh Pergerakan Candra Superstore Terhadap Kinerja Jaringan Jalan Disekitarnya - Tanjung, Novri Yanti Purba; Sulistyorini, Rahayu; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
Bandar Lampung as a central economic city in Lampung. In terms of urban development, the mostprominent and rapidly is a shopping center, one of which is a shopping center Candra Superstore.The purpose of this research is to measure the traffic performance on the road and intersectionsthat being affected by Candra Superstore, as well as measuring the impact from the Candra's latemovement which is in this case is about the long queue and delays of vehicles that line up in frontof the entrance of the store that cause the traffic issues around the store, so that this problem couldbe solved.From the research that has been done, Candra Superstore traffic flow affected by the vehicle thatline up in front of the store and resulted in high traffic jam especially at the peak hours around ,because the vehicle is out of Candra lead to delays and long queues resulting congestion is quitehigh traffic jam in front of the line up Candra, especially at peak hours at 16:00 -17.00.Keywords: free flow speed, degree of saturation, capacity, long queues, delays at intersections